2020
DOI: 10.3390/en13102607
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency in Transportation along with the Belt and Road Countries

Abstract: China’s huge investment in the “belt and road initiative” (BRI) may have helped improve the economic level of participating countries, but it may also be accompanied by a substantial increase in greenhouse gas (GHG) emissions. The BRI corridors aim to bring regional stability and prosperity. In such efforts, energy efficiency due to increased transport has been overlooked in the recent literature. This paper employed a data envelopment analysis of the slack-based measurement (SBM) for bad output to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…Based on the findings, the efficient implementation of energy sources in ASEAN's rural sector will reduce environmental contamination, especially in the long run. It is supporting the argument that advanced energy sources reduce greenhouse gas emissions in agriculture, which is beneficial to the environment [24,[63][64][65][66][67][68][69]. The tendency of people towards cities is not a problem in the short run, so in the long run, it significantly increases the ecological footprint.…”
Section: Resultssupporting
confidence: 53%
“…Based on the findings, the efficient implementation of energy sources in ASEAN's rural sector will reduce environmental contamination, especially in the long run. It is supporting the argument that advanced energy sources reduce greenhouse gas emissions in agriculture, which is beneficial to the environment [24,[63][64][65][66][67][68][69]. The tendency of people towards cities is not a problem in the short run, so in the long run, it significantly increases the ecological footprint.…”
Section: Resultssupporting
confidence: 53%
“…Similarly, Akbar et al [43] found that energy efficiency can reduce CO 2 emission; however, FDI and GDP will lead to an increase in CO 2 emission. In addition, Akbar et al [44] also analyzed the transport energy efficiency by taking two years as a pre-and post-BRI case, showing that, after the BRI, there is an increase in economic activity but a decline in transport energy efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reducing greenhouse gases in transport policies is a topic which is researched from many perspectives, spanning from transport efficiency [39,40], transport costs and emissions factors [41,42], transport modes in the EU [43,44] and more recently the use of big data [45,46] for designing mobility policies as well as technology transfer and innovation [47]. A clear gap in literature is the analysis of alternative policy instruments that focus on demand-side policies.…”
Section: Current and Planned Transport Policiesmentioning
confidence: 99%